Therapeutic potential of common Phytoestrogens found in traditional Chinese medicine in chronic kidney diseases - Liu, Tongtong; Li, Minghan (Frontiers in Pharmacology, 2025)
In recent years, phytoestrogens in traditional Chinese medicine (TCM)—a class of estrolike active components naturally occurring in medicinal plants—have gradually emerged as a research hotspot in the treatment of various diseases due to their multi-target regulatory potential. These metabolites are abundant in TCM, and an increasing body of evidence indicates that they have beneficial effects in chronic kidney diseases. Research demonstrates that phytoestrogens can alleviate renal pathological damage by regulating the expression of pro-inflammatory cytokines, reducing oxidative stress, and inhibiting the activation of fibrosis pathways. The application of phytoestrogens as a therapeutic strategy for chronic kidney diseases is highly promising. This review comprehensively summarizes the status of TCM phytoestrogens in chronic kidney disease research and elaborates in detail on various types of these compounds, such as baicalin and puerarin, as well as their protective effects on chronic kidney disease observed in animal and cell experiments. Additionally, we highlight the advantages of TCM phytoestrogens in the regulation of chronic kidney disease and discuss their potential clinical significance and future research directions in this field. These findings will provide a promising avenue for the development of drugs aimed at treating chronic kidney disease.